Passive Imperatives in Indonesian - I Nyoman Udayana (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2022)
An imperative clause is understood as a construction in which the subject is commonly filled by a second person but it is licitly dropped and the verb that co-occurs with it is commonly realized by a basic form in Indonesian. An active clause, on the other hand, contains an obligatory subject, the verb inflected with meN verbal prefix, and an object that makes the sentence readily transformed into its passive clause counterpart. Given the characteristic contrasts between an imperative clause and an active clause in Indonesian, it seems to be impossible to derive a passive imperative. However, imperative passives are available in Indonesian. The present study aims to uncover the issues of imperative passives in Indonesian. The study employs a descriptive qualitative method. Most of the data for the study were obtained from Leipzig Corpora and the remaining data were elicited from other speakers of Indonesian. Adopting the theory of a speaker commitment hypothesis for the analysis, the findings show that Indonesian has a passive imperative. This support can be evidenced by the fact that an imperative passive can be associated with a complex sentence construction in which the subject of the passive imperative clause can be recovered from the main clause thereby corroborating the idea that passive imperatives operate on a par with negative imperatives which possess prototypical passive constructions.